Employer behavior human resource management research and teaching in Germany and Austria - Dudo von Eckardstein; Stefan Konlechner (Management Revue, 2011)
Employer behavior ('Arbeitgeberverhalten') plays an essential role when it comes to understanding Human Resource Management (HRM). However, rather few studies actually seem to take the concrete behavior of organizations as employers into account. Instead, German textbooks and journals are replete with examples of 'good practices' in HRM. We argue that, as a result, there is a growing discrepancy between HRM in research/teaching and practice, which unquestionably is a problematic development in an applied science like HRM. Based on our analysis of five leading German textbooks on HRM and five volumes of the German Journal of Research in Human Resource Management (2005-2009), we highlight current gaps in the academic discussion and we derive some theses concerning the current state of the discussion. Finally, we discuss our findings and highlight some avenues for further research in our field.
Keywords: M12; M14; 650; HRM; employer behavior; textbook analysis; bad practice